Critical assessment of the world the movement of children at school age - Leães Filho, Wenceslau Virgilio Cardoso (Journal of Physical Education (Maringá), 2008)
This work was characterized as a case study which had as objective to analyse aspects of the children\’s world of movement. To accomplish this objective the following questions were formulated: a) How do children demand their bodies? What do they think that the body is able to do regarding movements? b) Where and in what spacial conditions the children move? Is their space for movement sufficiently near, stimulating and open? c) What do children play and move with? d) What norms and social factors have influence upon the life of movement of the children? How do children play in groups? e) How long can the children play and move? Is that time really free? The study was conducted in two schools of different social realities. One public school of suburb area, of low social level, and other a private school of high social level, both in Santa Maria, RS. From each school a fourth grade child was selected. For each child a diary was elaborated, by means ofpartipating observation and interviews. The data was analyzed by social interactions based on theories of symbolic interactionism and social dramaturgy. It may be concluded that social and physical environment determine fundamental differences in the experiment of movement of the children. Further studies to investigate children who live in different conditions from those described in this study are suggested.